Bank Deposit and Credit Policy Management in the Field of Individual Customer Service - Varkulevich, Tatyana V.; Pyzhov, Andrey S.; Titova, Natalya Y. (International Journal of Criminology and Sociology, 2022)
The article is devoted to the problem of individual customer service quality improvement in the field of provided deposit and credit services. This problem is a priority in determining any commercial bank strategy, since both deposit and credit policies determine the effectiveness of a credit institution development, which largely depends on the level of customer satisfaction. This study aims to determine the management aspects of the deposit and credit policy improvement in the field of commercial bank customer servicing. In the course of the work, they used the elements of system analysis, statistical research methods (summary and grouping, calculation of average values), and SWOT analysis. To assess customer satisfaction, the authors studied the Internet reviews of the largest regional bank of the Primorsky Territory of Russia - PJSC SKB of Primorye "Primsotsbank". The use of the indicated methods in the study made it possible to assess the quality of services provided to clients, identify the problems in their service sector, and develop the measures for their elimination. The results obtained are the basis for making managerial decisions to improve the deposit and credit policy of the studied bank and can be used in commercial banks' practice.